Economic Administration Reforms Commission Earc II/Report No.8 Towards the Successful Implementation of the Seventh Plan: an Overview of Economic Administration - Planning Commission (Planning Commission, 2022)
I have great pleasure in presenting herewith the last report of the Economic Administration Reforms Commission. It aims at providing an overview of economic administration, particularly from the point of view of ensuring the successful implementation of the Seventh Plan. Upto a point, it recapitulates the recommendations in our previous 37 reports. In addition, it deals with a number of new issues which will primarily need consideration by the Planning Commission, while most of the others will no doubt be considered at meetings of Secretaries which the Cabinet Secretary convenes for considering EARC Reports.
Planning Commission Government of India